Placing Portuguese Right-Wing Populism Into Context: Analogies With France, Italy, and Spain - Biscaia, Afonso (2021)
This chapter examines the discourse of the Portuguese right-wing populist André Ventura and compares it with his close counterparts, Santiago Abascal, Marine Le Pen, and Matteo Salvini. The empirical analysis is focused on the 2021 presidential campaign and looks at Twitter and YouTube as parts of an integrated political communication strategy that are used as tools of exposure and message dissemination. The results show how André Ventura appropriates the features of right-wing populism but adapts those to the Portuguese specific context as a strategy to gain both wider media visibility and popular support.